Nikolaj Glubokowskij und Adolf von Harnack - Druzhinina, Jekaterina (Hyperboreus, 2016)
The paper sketches life and academic activities of N. N. Glubokovsky (1863–1937), a professor of the Saint Petersburg Theological Academy. Stress is laid on his historical and philological studies of Bible and church history. The author also outlines the role of A. von Harnack in Glubokovsky’s life and career, who much appreciated his master’s thesis on Theodoret of Cyrus.